Investigating Single- Versus Multiple-Source Approaches to Communicating Health Messages Via an Online Simulation - Jongenelis, Michelle; Pettigrew, Simone; Wakefield, M.; Slevin, Terry; Pratt, I.; Chikritzhs, Tanya; Liang, Wenbin (2018)
Purpose: To assess whether exposing drinkers to information about the alcohol–cancer link via multiple and diverse sources in an online simulation produces larger improvements in attitudes and intentions relative to exposure to a single source of information. Design: Experimental; unequal randomization with respondents allocated to either the single-source (20%) or multiple-source condition (80%). Alcohol-related behavioral intentions were assessed preexposure and postexposure. Setting: Australia. Participants: A total of 2087 drinkers consuming alcohol at least twice per month. Measures: Scales were used to assess attitudes toward the messages (believability, convincingness, and personal relevance) and behavioral intentions (extent to which participants believed that they should and would reduce their alcohol consumption and their intention to consume 5 or more drinks in a single session). Analysis: Hierarchical linear regression. Results: Source condition was significantly associated with all 3 attitudinal variables (P < .001). Those exposed to an alcohol warning statement from multiple sources found the message more believable, convincing, and personally relevant compared to those exposed to a warning statement via a single source. They also reported significantly greater change preexposure to postexposure on the 2 behavioral beliefs that they should (ΔM = 0.25 vs ΔM = 0.09) and would (ΔM = 0.23 vs ΔM = 0.00) reduce their current alcohol consumption (P < .001). Further, those in the multiple-source condition reported reduced intentions to consume 5 or more standard drinks in a single sitting (ΔM = 0.21 vs ΔM = 0.14; P < .001).Conclusion: Findings from the online simulation provide support for the suggestion that integrated approaches involving the combination of multiple sources to deliver a message produce superior outcomes compared to relying on a single source (eg, warning labels on alcoholic beverages).